ANALISIS PENGAWASAN PENGELOLAAN DANA DESA OLEH BADAN PERMUSYAWARATAN DESA DI DESA PANCA JAYA KECAMATAN MUARA KAMAN KABUPATEN KUTAI KARTANEGARA - Karina Novianti (ADMINISTRASI PUBLIK, 2020)
The purpose of this study was to find out how the supervision of village fund management by the Village Consultative Body in Panca Jaya Village, District of Muara Kaman, Regency of Kutai Kartanegara. This focus is the Supervision of BPD in Village Fund Management which includes preventive supervision, namely at the planning and implementation research stages and repressive supervision, namely at the administration, reporting and accountability stages. This research method is a qualitative descriptive research method, which becomes the informants in the study, namely village staff and staff of  BPD. With data collection techniques using interviews, observation and documentation study, with data analysis techniques performed by data collection, data reduction, data presentation and data insention.The results of this study indicate that the implementation of Preventive and Ressive supervision of village fund management by BPD is quite good, it's just that BPD does not have the authority to decide what actions to take if there is a mismatch between the activities carried out and the APBDes that have been legalized with village regulations. , BPD will only coordinate with the Inspectorate to follow up on the non-conformity.